Tudományos pálya - nemzetiszocialista háttérrel : Fritz Valjavec karrierépítésének politikai aspektusai - Orosz, László (Közép-Európai Közlemények, 2016)
During the course of the conference series that has proposed a reexamination of the interwar period, the matter of Fritz Valjavec’s (1909-1960) academic career path has arisen on numerous occasions in regards to Hungarian-German relations. Therefore this current work deliberately chooses to examine not Valjavec the academic, but rather the political relationships that shaped his career. Four cases shall be used to attempt to illustrate a National Socialist background and frame of reference. We shall discuss the high-level intervention that removed the administrative obstacles from his being able to resettle in Germany, followed by an examination of his membership and participation in various Nazi professional, social and political organizations. Furthermore, we shall take a closer look at his propagandistic endeavors in support of Nazi foreign policy and scientific policy and his intelligence work on behalf of the highest levels of political leadership. Finally we touch upon his academic work in an SS-controlled university department serving exclusively political ends. We come to the conclusion that Valjavec pursued politicized scholastic work that served Nazi Germany’s interests, fundamentally providing the groundwork for the Reich’s political expansion.